2021
DOI: 10.1038/s41372-021-00942-w
|View full text |Cite
|
Sign up to set email alerts
|

Association between early cerebral oxygenation and neurodevelopmental impairment or death in premature infants

Abstract: Objective To assess the relationship between cerebral oxygenation in the first 72 h of life and neurodevelopmental impairment (NDI) at 2 years corrected age in former premature infants. Study design Prospective observational cohort study of 127 infants <32 weeks GA at birth with cerebral oxygenation monitoring using NIRS in the first 72 h of life. Results Using a threshold cutoff for cerebral hypoxia, infants with NDI or death had increased duration of hypoxia (4 vs 2.3%, p = 0.001), which was more pronounced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 15 publications
0
9
0
Order By: Relevance
“…In extremely preterm infants, low cerebral oxygenation saturation during the first 96 h after birth is associated with increased risk of mortality and brain injury, including intraventricular hemorrhage and periventricular leukomalacia ( 46 , 47 ). Observational studies in very preterm infants have also reported that a higher burden of cerebral hypoxia during the first 72 h, and lower area under the curve for cerebral oxygenation saturation during the first two weeks of life was associated with neurodevelopmental impairment ( 48 , 49 ). These findings suggest that cerebral oxygenation monitoring might improve outcomes in the early neurocritical care of preterm infants.…”
Section: Introductionmentioning
confidence: 99%
“…In extremely preterm infants, low cerebral oxygenation saturation during the first 96 h after birth is associated with increased risk of mortality and brain injury, including intraventricular hemorrhage and periventricular leukomalacia ( 46 , 47 ). Observational studies in very preterm infants have also reported that a higher burden of cerebral hypoxia during the first 72 h, and lower area under the curve for cerebral oxygenation saturation during the first two weeks of life was associated with neurodevelopmental impairment ( 48 , 49 ). These findings suggest that cerebral oxygenation monitoring might improve outcomes in the early neurocritical care of preterm infants.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have so far investigated how measures of SO 2 and OEF obtained in the first days of life are associated with later neurodevelopmental outcomes in infants born very preterm with inconsistent results. Two cohort studies of infants born before 32 weeks GA indicated that a lower cerebral SO 2 in the first 72 h of life was associated with lower cognitive scores at 24 months CA (Alderliesten et al, 2019;Katheria et al, 2021). In a study of 67 infants born before 32 weeks GA, lower SO 2 in the first 2 weeks of life was associated with less optimal neurodevelopment at 2-3 years of age, while higher OEF on the first day of life was associated with lower motor scores (Verhagen et al, 2015).…”
Section: Discussionmentioning
confidence: 94%
“…17 A recent study by Katheria et al showed an increase in neurodevelopmental impairment in infants less than 32 weeks of gestation when the rScO 2 was less than 67%. 19 Each of these studies looked at premature infants during the first 72 hours of life.…”
Section: Discussionmentioning
confidence: 99%